Quality of life and screening on body dysmorphic disorder, depression, anxiety in septorhinoplasty: original report - Hohenberger, Ralph; Endres, Philipp; Salzmann, Irina; Plinkert, Peter K.; Wallner, Frank; Baumann, Ingo; Alt, Janes; Riedel, Frank; Lippert, Burkard M.; Bulut, Cem (The laryngoscope, 2023)
Objectives Septorhinoplasty (SRPL) can improve quality of life (QoL) in functional and aesthetical aspects of the nose. A key factor compromising postoperative satisfaction is symptoms of body dysmorphic disorder (BDD), defined by excessive concerns and distress over slight or imagined physical defects. Although a high prevalence of BDD in SRPL patients is evident, the effect of positive screening on BDD and other psychiatric disorders is understudied. It was hypothesized that patients screening positive for BDD, depression or anxiety do not show increased postoperative QoL. Methods A multicenter, prospective study including 259 patients. For psychiatric evaluation, the BDD concern questionnaire—aesthetic version and the Hospital Anxiety and Depression Scale were used; for disease-specific QoL the Rhinoplasty Outcomes Evaluation (ROE) and the Functional Rhinoplasty Outcome Inventory (FROI-17). Results In preoperative evaluation, 32.5% had a positive screening for BDD, 42.2% for increased anxiety, and 32.9% for depression. Mean QoL improved in the whole cohort (FROI total score: 54.4 ± 21.8 to 32.8 ± 23.7 and ROE: 32.3 ± 15.6 to 69.8 ± 23.1, both p < 0.001). Patients screening positive for BDD, depression or anxiety did show an increased postoperative QoL, but to a significantly lower degree and with lower pre- and postoperative QoL levels. Conclusions SRPL patients show a high prevalence of BDD symptoms, elevated anxiety, and depression. These subgroups show lower QoL levels and an impaired QoL increase after surgery. Rhinoplasty surgeons must be aware of the disorders and their symptoms, discuss potential concerns with the patients, and potentially refer them to a specialist. Level of Evidence Level 3 Laryngoscope, 2023